Uji Reliabilitas dan Validitas Skala Karakter Baik (SKB) untuk Siswa SMA/Sederajat Di Indonesia - Lutfiana, Aviva; Salma, Hasna Hafizhah; Winardy, Gary Collins Brata; Seniati, Ali Nina Liche (Journal of Research and Measurement in Psychology: JPPP, 2023)
Good character is a congruence of thought, feelings and behaviors that are in accordance with principles of morality. Since 2016 Indonesian education system attempts to develop good character in students using principles for encouraging character education (PPK, Penguatan Pendidikan Karakter). The principles of PPK are based on Pancasila, Indonesia national ideology. These five principles are religiosity, nationalism, independence, cooperation, and integrity. Currently, there are no instrument for measuring good character in accordance with the principle of PPK. This study aims to develop a reliable and valid measuring tool for good character that can be used for measuring good character in Indonesian high school students. In the development of this measurement, this study tests the reliability with discriminatory item analysis using SPSS v.21. Construct validity was measured using confirmatory factor analysis with JASP emulation MPlus, from which group norm was formed with average of 10 and standard deviation of 3. The subjects of this study are 728 Indonesian high school students. The result of this study show that the instrument can be deemed reliable with Cronbach alpha of 0.892. This instrument also shows model fit p-value of 0.000, SRMRS of 0.078 and GFI of 0.957, which can be interpreted as a reliable in term of measurement.